Measurement of CP asymmetries and branching fractions in charmless two-body B-meson decays to pions and kaons - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
We present improved measurements of CP-violation parameters in the decays B0→π+π−, B0→K+π−, and B0→π0π0, and of the branching fractions for B0→π0π0 and B0→K0π0. The results are obtained with the full data set collected at the Υ(4S) resonance by the BABAR experiment at the PEP-II asymmetric-energy B factory at the SLAC National Accelerator Laboratory, corresponding to (467±5)×106 B¯¯¯B pairs. We find the CP-violation parameter values and branching fractions: Sπ+π−=−0.68±0.10±0.03, Cπ+π−=−0.25±0.08±0.02, AK−π+=−0.107±0.016+0.006−0.004, Cπ0π0=−0.43±0.26±0.05, B(B0→π0π0)=(1.83±0.21±0.13)×10−6, B(B0→K0π0)=(10.1±0.6±0.4)×10−6, where in each case, the first uncertainties are statistical and the second are systematic. We observe CP violation with a significance of 6.7 standard deviations for B0→π+π− and 6.1 standard deviations for B0→K+π−, including systematic uncertainties. Constraints on the unitarity triangle angle α are determined from the isospin relations among the B→ππ rates and asymmetries. Considering only the solution preferred by the Standard Model, we find α to be in the range [71°,109°] at the 68% confidence level.